Exploring the Lived Experiences of Teachers and Learners in the Aral Reading Program: A Phenomenological Study - Torlao, Susan (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of teachers and learners in the implementation of the Academic Recovery and Accessible Learning (ARAL) Reading Program at Talabaan Elementary School. Anchored on Vygotsky’s Sociocultural Theory and Bandura’s Social Cognitive Theory, the research examined how instructional support, social interaction, and self-efficacy shape literacy development among struggling readers. A qualitative phenomenological research design was employed, utilizing semi-structured interviews and non-participant classroom observations. The participants included nine teachers and ten learners from Grades 3 to 6 who were purposively selected based on their direct involvement in the program. Data were analyzed thematically using Interpretative Phenomenological Analysis procedures. Findings revealed that teachers viewed literacy instruction as a moral responsibility that was both demanding and fulfilling, while learners initially experienced fear and low confidence but gradually developed improved self-esteem and engagement in reading activities. The ARAL Reading Program was implemented through adaptive, learner-centered strategies such as phonics instruction, guided reading, differentiated activities, and the use of multimodal instructional materials. Strong teacher-learner relationships characterized by patience, encouragement, and individualized support were found to be essential in enhancing learner participation and motivation. However, implementation challenges included heavy teacher workload, limited instructional resources, insufficient training opportunities, time constraints, and learner-related difficulties such as decoding struggles, low confidence, and socio-emotional barriers. Despite these challenges, the program was perceived to improve learners’ reading competence, confidence, and long-term educational engagement. Collaboration among teachers, parents, and school stakeholders was identified as crucial for sustaining literacy development. The study aligns with SDG 4 (Quality Education) by promoting inclusive and equitable literacy development, SDG 10 (Reduced Inequalities) by addressing learning disparities among struggling readers, and SDG 17 (Partnerships for the Goals) through the emphasis on collaborative literacy support systems. Its sustainability impact lies in strengthening educational, social, and institutional sustainability by improving foundational literacy skills, enhancing teacher support systems, and fostering community engagement in literacy development.